2010
DOI: 10.1088/0004-6256/140/5/1519
|View full text |Cite
|
Sign up to set email alerts
|

Activity in Geminid Parent (3200) Phaethon

Abstract: The asteroid (3200) Phaethon is widely recognized as the parent of the Geminid meteoroid stream. However, it has never shown evidence for ongoing mass loss or for any form of comet-like activity that would indicate the continued replenishment of the stream. Following an alert by Battams & Watson, we used NASA's STEREO-A spacecraft to image Phaethon near perihelion, in the period UT 2009 June 17-22, when the heliocentric distance was near 0.14 AU. The resulting photometry shows an unexpected brightening, by a f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
247
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(251 citation statements)
references
References 47 publications
(51 reference statements)
4
247
0
Order By: Relevance
“…All these objects may be related to a precursor body that disintegrated ∼10 3 yr ago (Ohtsuka et al 2006). Evidence for modern-day mass loss comes from the observed brightening of Phaethon by a factor of two within a few hours of perihelion (R = 0.14 AU) in 2009 (Jewitt & Li 2010). This rapid brightening cannot be due to scattering from the ∼5 km diameter nucleus alone and, instead, indicates transient mass loss with the ejection of ∼10 8 a 1 kg of particles each a 1 mm in radius.…”
Section: Observations Of Active Asteroidsmentioning
confidence: 97%
See 2 more Smart Citations
“…All these objects may be related to a precursor body that disintegrated ∼10 3 yr ago (Ohtsuka et al 2006). Evidence for modern-day mass loss comes from the observed brightening of Phaethon by a factor of two within a few hours of perihelion (R = 0.14 AU) in 2009 (Jewitt & Li 2010). This rapid brightening cannot be due to scattering from the ∼5 km diameter nucleus alone and, instead, indicates transient mass loss with the ejection of ∼10 8 a 1 kg of particles each a 1 mm in radius.…”
Section: Observations Of Active Asteroidsmentioning
confidence: 97%
“…Young's moduli Y = (10-100) × 10 9 N m −2 are typical for rock (Pariseau 2006, p. 474). If converted into kinetic energy with efficiency η, thermal strain energy can generate fractured material with speeds (Jewitt & Li 2010) …”
Section: Thermal Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…There are other hypothesised effects that have yet to be conclusively demonstrated to explain observed 'activity', such as thermal cracking, electrostatic levitation of dust, or radiation pressure accelerating dust away from the surface (Jewitt et al 2015c). We also exclude dynamically asteroidal objects (i.e., with T J > 3.05) outside of the asteroid belt for which activity has been detected, e.g., (3200) Phaethon (Jewitt and Li 2010;Li and Jewitt 2013;Hui and Li 2017) and 107P/(4015) Wilson-Harrington (Fernandez et al 1997). See Jewitt et al (2015c) and references therein for more extensive discussion of active asteroids beyond our definition of 'MBC'.…”
Section: Definitions: Active Asteroids and Main Belt Cometsmentioning
confidence: 99%
“…Although these objects are almost certainly active when in the SOHO fields of view (0.15 au), this activity is not necessarily due to the traditional "cometary" mechanism of sublimation of volatile ices. Jewitt & Li (2010) and Li & Jewitt (2013) argue that (3200) Phaethon produces dust near perihelion (0.14 au) via non-traditional means such as thermal fracture, while Kimura et al (2002) and others have shown that silicates and other refractory materials begin to sublimate at even smaller distances.…”
Section: Introductionmentioning
confidence: 99%